New genetic sources of resistance in the genus Phaseolus to individual and combined aluminium toxicity and progressive soil drying stresses - Butare, L.; Rao, Idupulapati M.; Lepoivre, Philippe; Polanía Perdomo, José A.; Cajiao V., César Hernando; Cuásquer, Juan B.; Beebe, Stephen E. (Springer, 2011)
Bean species and genotypes show wide phenotypic variability in relation to aluminium (Al) resistance and progressive soil drying. The objective of this study was to identify and characterize sources of resistance to Al toxicity and progressive soil drying among six genotypes of common bean (Phaseolus vulgaris), four of runner bean (P. coccineus), and one of tepary bean (P. acutifolius), using hydroponic and soil cylinder screening methods. One experiment on hydroponic screening of Al resistance was carried out using a basal nutrient solution with and without 20 μM Al. Two experiments were carried out using two oxisols in 80 cm long soil cylinders with high Al (HAl) and low Al (LAl) saturation treatments. The three experiments showed an average of 36.9–53.5% inhibition of root growth with HAl compared with LAl treatments. Differences in root development and distribution were observed among genotypes and species. Two accessions of P. coccineus (G35346-2Q, G35464-5Q) and one Andean common bean genotype (ICA Quimbaya) were outstanding in root and shoot growth in the HAl treatments. P. coccineus accession (G35346-3Q) was outstanding under combined stress of Al-toxic acid soil and progressive soil drying. Accessions of P. coccineus may represent unique sources of Al resistance for the improvement of common bean through interspecific crosses.